Malassezia and Parkinson's Disease - Laurence, Martin; Benito-León, Julián; Calon, Frédéric (Frontiers in Neurology, 2019)
Parkinson’s disease (PD) is a common debilitating neurodegenerative disease caused by a loss of dopamine neurons in the substantia nigra within the central nervous system (CNS). The process leading to this neuronal loss is poorly understood. Seborrheic dermatitis (SD) is a common benign inflammatory condition of the skin which mainly affects lipid-rich regions of the head and trunk. SD is caused by over proliferation of the lipophilic fungus Malassezia. PD and SD are strongly associated. The increased PD risk following an SD diagnosis (OR=1.69, 95% CI 1.36, 2.1; p < 0.001) reported by Tanner and colleagues remains unexplained. Malassezia were historically considered commensals confined to the skin. However, many recent studies report finding Malassezia in internal organs, including the CNS. This raises the possibility that Malassezia might be directly contributing to PD. Several lines of evidence support this hypothesis. AIDS is causally associated with both parkinsonism and SD, suggesting that weak T cell-mediated control of commensal microbes such as Malassezia might contribute to both. Genetic polymorphisms associated with PD (LRRK2, GBA, PINK1, SPG11, SNCA) increase availability of lipids within human cells, providing a suitable environment for Malassezia. Three LRRK2 polymorphisms which increase PD risk also increase Crohn’s disease risk; Crohn’s disease is strongly associated with an immune response against fungi, particularly Malassezia. Finally, Malassezia hypha formation and melanin synthesis are stimulated by L-DOPA, which could promote Malassezia invasiveness of dopamine neurons, and contribute to the accumulation of melanin in these neurons. Although Malassezia’s presence in the substantia nigra remains to be confirmed, if Malassezia plays a role in PD etiology, antifungal drugs should be tested as a possible therapeutic intervention.